Acute care of at-risk newborns : a resource and learning tool for health care professionals - E. Boulton, Jill (2020)
"ACoRN (short for Acute Care of at-Risk Newborns) was developed by an expert group of Canadian neonatal care providers and educators. Since launching in 2005, ACoRN has been taught across Canada and internationally, in formats varying from 1- to 3-day local, regional, or provincial/territorial workshops to module-based learning over a period of weeks. As with many education programs, ACoRN has evolved from didactic sessions and tabletop simulations to the hands-on, simulation-based workshops utilized today. Updates to the first edition of the text were published in 2010 and 2012 to add new content (on therapeutic hypothermia, for example)"--
Includes bibliographical references and index.
Keywords: Neonatal intensive care; Newborn infants -- Medical care; Newborn infants -- Diseases